Discrimination between glutaminyl-tRNA synthetase and seryl-tRNA synthetase involves nucleotides in the acceptor helix of tRNA. - Rogers, M J (1988)
Analysis of the in vivo amber suppressor activity of mutants derived from two Escherichia coli serine tRNAs shows that substitution of 2 base pairs in the acceptor helix changes a serine suppressor tRNA to an efficient glutamine acceptor. Determination of the amino acid inserted in vivo into protein by this tRNA shows that these changes reduce the tRNA recognition by seryl-tRNA synthetase while increasing that of glutaminyl-tRNA synthetase. This implies that misaminoacylation in vivo is dependent on the competition by different synthetases for the tRNA. In addition, the "translational efficiency" of tRNA is an integral part in observing misaminoacylation in vivo.